The wedding game - Quinn, Meghan (Montlake, 2021)
"Luna Rossi is a veritable crafting genius--she can bedazzle and bead so hard her Etsy site is one of the hottest in the world. So it's only natural that Luna would convince her brother and his husband-to-be to compete on The Wedding Game, a 'do-it-yourself' TV show, for the title of Top DIY Wedding Expert. As a jaded divorce lawyer, Alec Baxter scoffs at weddings and romance. But when his recently engaged brother begs him to participate in The Wedding Game, Alec grudgingly picks up a glue gun and prepares for some family bonding. Both fierce competitors, Luna and Alec clash on national TV as harsh words and glitter fly with abandon. But as they bicker over color swatches and mood boards, they find themselves fighting something else: their growing mutual attraction. While Luna is torn between family loyalty and her own feelings, Alec wonders if he might have been wrong about love and marriage all along"--Back cover.